SAFETY, EFFICACY, AND EFFECTIVENESS OF BRENTUXIMAB VEDOTIN IN THE TREATMENT OF RELAPSED OR REFRACTORY CD30+ HODGKIN LYMPHOMA AFTER AUTOLOGOUS STEM CELL TRANSPLANTATION: A SYSTEMATIC REVIEW (REMUNOM, 2026)
This systematic review reassessed the efficacy, safety, and impact on quality of life of Brentuximab Vedotin (BV) in treating relapsed/refractory (R/R) CD30+ Hodgkin lymphoma after autologous stem cell transplantation (ASCT). The review followed the Cochrane Handbook for Systematic Reviews of Interventions, with results reported according to PRISMA guidelines. The initial search was conducted on December 11, 2024. A total of 2291 studies were identified; eight met the eligibility criteria, including one phase 3 randomized controlled trial (RCT) and seven retrospective observational studies. In total, 1628 patients received BV after relapse or progression post ASCT, while 924 received comparator therapies such as chemotherapy, checkpoint inhibitors, anthracyclines, gemcitabine, pembrolizumab, and radiotherapy. Risk of bias assessments using RoB 2.0 and ROBINS-I indicated variable risk, ranging from some concerns to moderate or serious. The certainty of evidence, assessed using the GRADE approach, ranged from moderate to low, resulting in a weak recommendation. Overall, BV either as monotherapy or combined with other treatments, showed promising potential for inducing disease remission in patients with R/R CD30+ Hodgkin lymphoma after ASCT. However, limitations in the current evidence underscore the need for more robust, high-quality studies to confirm and strengthen these findings.